Dramatization of Poetry in the Diwan Tassiliya by Ezzedine Mihoubi - lebachi, abdelkader (El Omda in Linguistics and Discourse Analysis, 2019)
Abstract: This reading is intended to examine the stratification of the writing layers with their wide and endless space, which is full of different kinds, overlapping with no date and one color, and each of these races maintaining their boundaries is difficult and difficult. Or so, as Jacobson decided: the border between poetry and prose has become less stable than China's administrative borders. Poetry, like the theater through their long history, had a special place, weren’t they a single one. Wasn’t the theater at the beginning poetry? Doesn’t the literary and artistic history of the Greek theater remind us of the great poets: Asechylus, Sophocles, and Europides? In modern Arabic poetry, they have come close to the masses of poetry through the mechanism of drama. In our contemporary Algerian poetry, (Tassilia) presents to the poet Azzedine Mihoubi a clear example of the drama of poetry through the humanization of personalities in intensive dialogues, in the presence of multiple voices, working on the written space and investing in different channels of reporting